(untitled) (Human Factors in Design, 2023)
Rehabilitation in the Brazilian public health care system (SUS) involves the continuous contact of several sectors to assist the patient. Improvements in the structure of a SUS orthosis unit are analyzed and recommended. The Macroergonomic Analysis of Structure (MAS) is used, through observation and semi-structured interview. The analysis indicated high formalization in the service and the opportunity to improve the means of integration. These improvements do not change the organizational structure and can contribute to the forecasting of AT demand, patient flow management and communication between UOPM and municipal health units, reducing time wastage and patient waiting.